PRODUCTION PERFORMANCE O LACTATING NILI-RAVI BUFFALOES UNDER THE INFLUENCE OF SOMATOTROPIC HORMONE WITH VARYING LEVEL OF DIETARY ENERGY - M. A. Jabbar; I. Ahmad; T. N. Pasha; M. Abdullah; S. Riffat (Journal of Animal and Plant Sciences, 2012)
The study was conducted to determine the effect of dietary energy on milk yield and its composition under the influence of bovine somatotropic (bST) hormone in Nili Ravi buffaloes. Multiparous buffaloes (n=12) at mid lactation and similar level of production were selected and randomly divided into three groups (A, B and C) with four animals in each group in a completely randomized design. All the experimental animals were injected bST at fortnightly interval after 60 ± 3 days postpartum for a period of 90 days. The nutritional requirements of these animals were met through total mixed ration with different densities of energy (high energy density, 115 %; medium energy density, 100 %; and low energy density, 80 % of NRC, 2001 standards). The increase in milk yield on high energy density (HED) ration was significantly higher (P<0.05) than medium energy density (MED) and low energy density (LED) diets. However, the difference was non significant between MED and LED rations. The values for feed efficiency were 0.61, 0.66 and 0.74 on LED, MED and HED diets and difference was significant (P<0.05) with best efficiency on ration HED. Difference in nutrient intake on LED ration was significantly higher (P<0.05) (except for ether extract) than other two other rations. However, the milk composition and body weight gain were similar on all rations. Results indicated that 15% higher energy than recommended by NRC, favored milk production in Nili-Ravi buffaloes when they were given bST hormone.
Keywords: Bovine somatotropic hormone; Nili-Ravi buffaloes; milk yield; dietary energy